Care of the Certified Psychiatric Patient in the General Hospital: The Saskatoon Project - Smith, Colin M. (1963)
The effect of admitting a random selection of 42 committed psychiatric patients to an ordinary, open general hospital psychiatric ward was studied. A control group of 44 regular psychiatric patients was formed for comparison purposes. Differences were studied by rating scales of behaviour and psychopathology and by nursing and medical observations. Though differences in ages and psychopathology were marked, the differences in behavioural problems were slight. The results are consistent with the belief that a well-trained staff can now manage practically all psychiatric admissions in a general hospital.